The financial crisis and the free market cure : why pure capitalism is the world economy's only hope - Allison, John A. (New York : McGraw-Hill, 2013)
The Financial Crisis and the Free Market Cure argues against current financial regulations and proposes a cure to the economy's ills. John A. Allison presents the groundbreaking theory that capitalism is the only economic-political system that allows freedom of thought and rewards those who offer the most productive ideas, products, and services.
Fundamental themes -- What happened? -- Government monetary policy: the Fed as the primary cause -- FDIC insurance: the background cause -- Government housing policy: the proximate cause -- The essential role of banks in a complex economy: the liquidity challenge -- The residential real-estate-market bubble and financial-market stress -- Failure of the rating agencies: the subprime mortgage market and its impact on capital markets -- Pick-a-payment mortgages: a toxic product of FDIC insurance -- How Freddie and Fannie grew to dominate the home mortgage lending business -- Fair-value accounting and wealth destruction -- Derivatives and shadow banking: a misunderstanding -- The myth that'deregulation' caused the financial crisis -- How the SEC made matters worse -- Market corrections are necessary, but panics are destructive and avoidable -- TARP (Troubled Asset Relief Program) -- What we could have--and should have--done -- The cure for the banking industry: systematically move toward pure capitalism -- Some political cures: government policy -- Our short-term path and how to end unemployment -- The deepest cause is philosophical -- The cure is also philosophical -- How the United States could go broke -- The need for principled action.
'How destructive banking reform is killing the economy'--Book jacket.
Includes bibliographical references (p. 255-266) and index.
Keywords: Capitalism; Financial crises -- United States; Financial services industry -- Law and legislation -- United States